A Matter of Balance: About the Abstract Goals of Imprisonment and Ambiguous Tasks of Dutch Prisons - Molleman, T. (The prison journal, 2017)
According to national and international inspectorates, considerable differences are found in the implementation of prison sentences within countries. This is not only problematic for the legal security of society and inmates, prison organizations themselves do not know exactly for what they are deemed responsible. Although key goals of imprisonment may be clear, complex ambiguities seem to be at work. We scrutinize the specific situation of the Dutch prison system to show how implementation differences can arise within a seemingly detailed regulatory framework. Furthermore, some international comparisons are provided as well as some directions to solve the ambiguities.